Foreign trade-economic growth nexus: Evidence from Nigeria - Nosakhare L. Arodoye; Milton A. Iyoha (CBN Journal of Applied Statistics, 2014)
This study examines the nexus between foreign trade and economic growth in Nigeria using quarterly time-series data for 1981Q1 through 2010Q4. In order to fully account for feedbacks, a vector autoregressive model is utilized. The results show that there is a stable, long- run relationship between foreign trade and economic growth. The variance decomposition results show that the predominant sources of Nigeria economic growth variation are due largely to "own shocks" and foreign trade innovations. The study therefore recommends adoption of trade expansion policies as a means of accelerating economic growth in Nigeria.
Keywords: F14; O41; 330; Foreign Trade; Economic Growth; VAR; Nigeria